EMAS SEBAGAI INSTRUMEN SAFE HAVEN DALAM PORTOFOLIO MODERN: TINJAUAN LITERATUR SISTEMATIS PASCA KRISIS GLOBAL - Imelda Regina Sumayku; Novie P. Sibilang (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to identify, evaluate, and synthesize empirical evidence regarding the role of gold as a safe-haven, hedge, and diversifier instrument in modern portfolios, employing a Systematic Literature Review (SLR) approach within the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Articles were analyzed using thematic synthesis, involving a coding process based on crisis characteristics, econometric methods, and market types. Out of 309 articles identified across the Scopus, Web of Science, ScienceDirect, and Google Scholar databases, 20 met all inclusion criteria for the 2020–2026 period. The synthesis results indicate that gold's effectiveness as a safe haven is conditional and dynamic rather than universal and static: gold proved effective in protecting portfolio value during structural financial crises—such as the 2008 Global Financial Crisis—and prolonged geopolitical tensions like the Russia-Ukraine conflict, yet it lost its protective function during the initial phases of sudden liquidity crises, such as the COVID-19 pandemic. Key moderating factors identified include crisis typology, gold market volatility, interest rate policies, exchange rate dynamics, and market characteristics—including structural differences between developed markets and emerging markets like Indonesia. The emergence of crypto-assets has not fully displaced gold's position; instead, it creates opportunities for strategic complementarity that can enhance risk-adjusted returns in modern portfolio construction. Keywords: safe haven; gold; systematic literature review; portfolio management; cryptocurrency   Abstrak: Penelitian ini bertujuan mengidentifikasi, mengevaluasi, dan mensintesis bukti empiris mengenai peran emas sebagai instrumen safe haven, hedge, dan diversifier dalam portofolio modern melalui pendekatan Systematic Literature Review (SLR) dengan kerangka Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Artikel dianalisis menggunakan thematic synthesis dengan proses coding berdasarkan karakteristik krisis, metode ekonometrika, serta tipe pasar. Dari 309 artikel yang diidentifikasi melalui basis data Scopus, Web of Science, ScienceDirect, dan Google Scholar, sebanyak 20 artikel memenuhi seluruh kriteria inklusi untuk rentang periode 2020–2026. Hasil sintesis menunjukkan bahwa efektivitas emas sebagai safe haven bersifat kondisional dan dinamis, bukan universal dan statis: emas terbukti efektif melindungi nilai portofolio dalam konteks krisis finansial struktural seperti Global Financial Crisis 2008 serta tekanan geopolitik berkepanjangan seperti konflik Rusia–Ukraina, namun kehilangan fungsi protektifnya selama fase awal krisis likuiditas mendadak seperti pandemi Covid-19. Faktor-faktor moderasi utama yang teridentifikasi mencakup tipologi krisis, tingkat volatilitas pasar emas itu sendiri, kebijakan suku bunga, dinamika nilai tukar, serta karakteristik pasar, termasuk perbedaan struktural antara pasar maju dan emerging market seperti Indonesia. Kehadiran aset kripto tidak sepenuhnya menggantikan posisi emas, melainkan membentuk peluang komplementaritas strategis yang dapat meningkatkan risk-adjusted return dalam konstruksi portofolio modern. Kata kunci: safe haven; emas; systematic literature review; manajemen portofolio;   cryptocurrency